Brave Wolf and the Thunderbird : tales of the people - Medicine Crow, Joseph, 1913- (Washington, D.C. : National Museum of the American Indian ; New York : Abbeville Press, 1998)
While hunting, Brave Wolf is snatched by a huge Thunderbird and taken to her nest on a high cliff so he can protect her chicks from a monster.
3.5
K-3
Keywords: Crow Indians -- Folklore; Tales -- Montana; Thunderbird (Legendary character) -- Legends; Thunderbird (Legendary character) -- Legends; Crow Indians -- Folklore; Indians of North America -- Montana -- Folklore; Folklore -- Montana; Thunderbird (Legendary character) -- Legends; Crow Indians -- Folklore; Native Americans -- Folklore -- Montana; Folklore -- Montana